2013
DOI: 10.1080/15298868.2012.682360
|View full text |Cite
|
Sign up to set email alerts
|

Self-views of African-American Youth are Related to the Gender Stereotypes and Ability Attributions of Their Parents

Abstract: We examined relations among African American mothers’ (N = 392) stereotypes about gender differences in mathematics, science, and reading performance, parents’ attributions about their children’s academic successes and failures, and their seventh and eighth grade children’s academic self-views (domain-specific ability attributions and self-concept). Parents’ stereotypes about gender differences in abilities were related to their ability attributions for their children’s successes and failures within academic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 33 publications
0
7
0
2
Order By: Relevance
“…Imagine, for instance, a teacher saying in front of her preschool group of children that the girls probably want to stay inside while the boys would probably prefer to play outside. Indirect evidence for such a transmission of gender stereotypes comes from research on parents' or teachers' gendered ability related expectations (e.g., Tiedemann, 2000; Rouland et al, 2013; see Jacobs et al, 2005, for a review). For instance, Upadyaya and Eccles (2014) found primary school teachers to rate boys as higher in math ability than girls, and girls as putting more effort into reading than boys, with these perceptions in turn predicting children's ability self-concepts in math and reading.…”
Section: Introductionmentioning
confidence: 99%
“…Imagine, for instance, a teacher saying in front of her preschool group of children that the girls probably want to stay inside while the boys would probably prefer to play outside. Indirect evidence for such a transmission of gender stereotypes comes from research on parents' or teachers' gendered ability related expectations (e.g., Tiedemann, 2000; Rouland et al, 2013; see Jacobs et al, 2005, for a review). For instance, Upadyaya and Eccles (2014) found primary school teachers to rate boys as higher in math ability than girls, and girls as putting more effort into reading than boys, with these perceptions in turn predicting children's ability self-concepts in math and reading.…”
Section: Introductionmentioning
confidence: 99%
“…The result concerning children's sex showed that the mothers of girls and boys were equally represented in all of the identified attribution patterns. One reason for the fact that in the present study no sex differences were found is that previous studies have shown that sex differences are subject specific (i.e., girls' abilities are rated higher in reading and boys' abilities in mathematics; e.g., Hess & McDevitt, 1986;Holloway et al, 1986;Jacobs & Eccles, 1992;Parsons et al, 1982;Rouland et al, 2013;Räty et al, 2002;Räty, Kasanen, & Honkalampi, 2006;Räty, PATTERNS OF PARENTAL ABILITY ATTRIBUTIONS 30 Kasanen, & Kärkkäinen, 2006;Yee & Eccles, 1988). However, in the present study, parents' ability attributions regarding their children's performance in mathematics and in reading were not separated.…”
Section: Attributionsmentioning
confidence: 51%
“…Besides of children's academic performance, also children's sex has been shown to play a role in parental attributions. Parents typically attribute boys' success in math to ability and girls' failure in math to lack of ability (e.g., Hess & McDevitt, 1986;Holloway et al, 1986;Jacobs & Eccles, 1992;Parsons, Adler, & Kaczala, 1982;Rouland, Rowley, & Kurtz-Costes, 2013;Räty, Vänskä, Kasanen, & Kärkkäinen, 2002;Yee & Eccles, 1988), whereas girls' competence in their native language is rated more positively than boys' (e.g., Rouland et al, 2013;Räty, Kasanen, & PATTERNS OF PARENTAL ABILITY ATTRIBUTIONS 10 Honkalampi, 2006;Räty, Kasanen, & Kärkkäinen, 2006), and boys' literacy failures are more likely attributed to lack of ability than girls' (Rouland et al, 2013). The results concerning sex differences in studies that combined performance in math and reading have been contradictory.…”
Section: Antecedents Of Parents' Ability Attributionsmentioning
confidence: 99%
“…Notably, female New Zealand elementary and middle school students underestimated their ability even when their mathematics achievement was higher than that of their male peers (Bonne, 2016). In a study of German 8-9-year olds, Dickhäuser and Meyer (2006) found that girls attributed success in mathematics less to high ability and failure in the subject more to low ability than boys. Similarly, in a meta-analysis of cross-national gender differences in mathematics using Trends in International Mathematics and Science Study (TIMSS) and Program for International Student Assessment (PISA) data, Else-Quest et al (2010) determined that boys showed more positive levels of mathematics confidence in almost all the participating countries.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the ability judgments of significant others (e.g., teachers) have held especial potential to impact mathematics self-concept (Dickhäuser and Stiensmeier-Pelster, 2003) and notably so for elementary school children (Marsh et al, 1998). Further, girls have relied on a perception of teacher evaluations of their mathematics ability to a greater extent than boys in forming attributions of their mathematics ability (Dickhäuser and Meyer, 2006). Erdogan and Şengul (2014) stressed the roles of quality of instruction and the classroom climate as central in influencing the development of students’ mathematics self-concept.…”
Section: Introductionmentioning
confidence: 99%